Absence of penile erections during paradoxical sleep. Peculiar penile events during wakefulness and slow wave sleep in the armadillo - Affanni, J.M. (2001)
The electroencephalogram (EEG) together with electromyogram (EMG) of the ischiocavernosus, bulbocavernosus and levator penis muscles were chronically monitored across behavioral states of the armadillo Chaetophractus villosus. This animal has a very long penis, which exhibits remarkable phenomena during wakefulness (W), slow wave sleep (SWS) and paradoxical sleep (PS). During W it remains retracted within a skin receptacle. During SWS penile protrusion can be observed together with very complex movements. Protrusion is a non erectile event during which the penis remains out of its receptacle but without rigidity. Penile erections are observed only during SWS. Contrasting with other mammals, no erections occur during PS. During this phase the penile muscles share the atonia of the body musculature characteristic of that phase. Some reflections on mechanisms of those penile events are presented.